2018
DOI: 10.1177/0892705718815529
|View full text |Cite
|
Sign up to set email alerts
|

Friction and wear characteristics of fibre-reinforced plastic composites

Abstract: The dominance of fibre-reinforced plastics in industries has enhanced the need for research to develop new composites and assess their properties. Among the various property analyses, tribological characteristics of the composites help to understand the friction and wear behaviour. This article presents a comprehensive survey on the tribological behaviour of polymeric composites, which includes the influence of various working parameters such as the velocity of sliding, sliding distance, pressure applied and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 96 publications
0
24
0
Order By: Relevance
“…[14][15][16][17] Various researchers have reported the abrasive wear studies of different types of composites. 18,19,[20][21][22][23][24][25][26][27][28] Carbon reinforced polymer matrix composites was subjected to wear and its behaviour was studied. It was reported that volume loss of the composite is related directly to abrading distance and specific wear rate is related inversely to applied load and abrasion distance.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] Various researchers have reported the abrasive wear studies of different types of composites. 18,19,[20][21][22][23][24][25][26][27][28] Carbon reinforced polymer matrix composites was subjected to wear and its behaviour was studied. It was reported that volume loss of the composite is related directly to abrading distance and specific wear rate is related inversely to applied load and abrasion distance.…”
Section: Introductionmentioning
confidence: 99%
“…These fibres have exhibited an on par and sometimes better characters than the man-made fibres like glasses and carbon. 4 -7 A natural fibre may not be used in its own form. Pre-treatment methods like treating with standard chemicals and heat treatment are done to improve the suitability of a natural fibre in a composite and also to improve its strengths.…”
Section: Introductionmentioning
confidence: 99%
“…Compounds with hydroxide groups, such as sodium hydroxide (NaOH), potassium hydroxide, and so on, are commonly called alkali, and the treatment is said to be alkalination. 23,24 Several research works have focussed on the influence of NaOH treatment on the mechanical strengths and other properties of the natural fibre composites. All these have proved that alkalination is one of the common methods of pretreatment and may be applicable for all-natural fibres.…”
Section: Alkali Treatmentmentioning
confidence: 99%